Interaction of Wnt pathway related variants with type 2 diabetes in a Chinese Han population - Zhou, Jian-Bo; Yang, Jin-Kui; Zhang, Bao-Hong; Lu, Jing (PeerJ, 2015)
Aims. Epistasis from gene set based on the function-related genes may confer to the susceptibility of type 2 diabetes (T2D). The Wnt pathway has been reported to play an important role in the pathogenesis of T2D. Here we applied tag SNPs to explore the association between epistasis among genes from Wnt and T2D in the Han Chinese population. Methods. Variants of fourteen genes selected from Wnt pathways were performed to analyze epistasis. Gene–gene interactions in case-control samples were identified by generalized multifactor dimensionality reduction (GMDR) method. We performed a case-controlled association analysis on a total of 1,026 individual with T2D and 1,157 controls via tag SNPs in Wnt pathway. Results. In single-locus analysis, SNPs in four genes were significantly associated with T2D adjusted for multiple testing (rs7903146C in TCF7L2, p = 3.21∗10−3, OR = 1.39, 95% CI [1.31–1.47], rs12904944G in SMAD3, p = 2.51∗10−3, OR = 1.39, 95% CI [1.31–1.47], rs2273368C in WNT2B, p = 4.46∗10−3, OR = 1.23, 95% CI [1.11–1.32], rs6902123C in PPARD, p = 1.14∗10−2, OR = 1.40, 95% CI [1.32–1.48]). The haplotype TGC constructed by TCF7L2 (rs7903146), DKK1 (rs2241529) and BTRC (rs4436485) showed a significant association with T2D (OR = 0.750, 95% CI [0.579–0.972], P = 0.03). For epistasis analysis, the optimized combination was the two locus model of WNT2B rs2273368 and TCF7L2rs7903146, which had the maximum cross-validation consistency. This was 9 out of 10 for the sign test at 0.0107 level. The best combination increased the risk of T2D by 1.47 times (95% CI [1.13–1.91], p = 0.0039). Conclusions. Epistasis between TCF7L2 and WNT2B is associated with the susceptibility of T2D in a Han Chinese population. Our results were compatible with the idea of the complex nature of T2D that would have been missed using conventional tools.
Keywords: Epistasis; Wnt pathway; Type 2 diabetes